Fungsi Mediasi Kepercayaan pada Pengaruh Kepuasan terhadap Loyalitas Pelanggan - Wahyudi, Wahyudi; Nurmiati, Nurmiati; Farild, Miftha; Bakhtiar, Fauziah (Jurnal Manajemen dan Kewirausahaan, 2021)
The purpose of this study is to verify the mediating role of trust on the linkage of customer satisfaction toward customer loyalty. The data for this study were collected through a survey of 216 bank customers in Makassar, and the responses were analyzed to assess the linkage of customer satisfaction toward customer loyalty with trust as mediating variable. The research findings indicate that in the banking industry, customer satisfaction and trust positively effect on customer loyalty. In addition, trust has not mediation effect between customer satisfaction and loyalty. This means that to increase customer loyalty, the banking industry must provide good service to customers, and pay strong attention to customer satisfaction and trust as well. Finally, this study makes an important contribution to the existing literature by conducting empirical research on the linkage among customer satisfaction, trust and customer loyalty.